High-density lipoprotein cholesterol as a prognostic marker for 90-day transplant-free mortality in hepatitis B virus-related acute-on-chronic liver failure - Ke Shi; Yi Zhang; Yanqiu Li; Xiaojing Wang; Ying Feng; Xianbo Wang (Frontiers in Cellular and Infection Microbiology)
BackgroundHepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is linked to dyslipidemia and inflammatory responses. This study aimed to investigate the correlation between high-density lipoprotein cholesterol (HDL-C) levels and 90-day transplant-free (TF) mortality in patients with HBV-ACLF.MethodsA prospective cohort of 287 patients with HBV-ACLF from Beijing Ditan Hospital was enrolled between January 2016 and December 2019. The prognostic accuracy of lipid profile parameters was evaluated by the area under the receiver operating characteristic curve (AUC), and the association between HDL-C levels and mortality was assessed using a restricted cubic spline analysis. Correlations between lipid profile parameters and inflammatory factors were analyzed. Kaplan–Meier curves were used to assess 90-day TF mortality, and log-rank tests were used for comparison analysis. These results were internally validated between January 2020 and December 2023 (n=125).ResultsPatients with lower HDL-C levels exhibited higher mortality rates (adjusted hazard ratio for HDL-C < 0.13 mmol/L: 4.04, 95% confidence interval: 1.35–11.85) compared with those in the reference group (with HDL-C levels above 0.36 mmol/L). An “L-shaped” association was observed between HDL-C levels and TF mortality. The prognostic value of HDL-C (AUC at day 90: 0.732) was comparable to the model for end-stage liver disease score of 0.729. Additionally, HDL-C levels were inversely correlated with interleukin (IL)-4, IL-6, and tumor necrosis factor-α (all P<0.05). In the training cohort, the 90-day TF mortality rates were 8.3%, 15.2%, 24.0%, and 43.2% for the extremely low, low, medium, and high-risk subgroups, respectively, while in the validation cohort, they were 4.5%, 18.5%, 31.2%, and 44.7%, respectively.ConclusionsHDL-C levels < 0.13 mmol/L were associated with increased 90-day transplant-free mortality in patients with HBV-ACLF. An inverse correlation was found between HDL-C levels and inflammatory markers.